Amyloid‐β processing in aged s100b transgenic mice is sex dependent - Wartchow, Krista Minéia; Rodrigues, Leticia; Swierzy, Izabela; Buchfelder, Michael; de Souza, Diogo Onofre; Gonçalves, Carlos Alberto; Kleindienst, Andrea (International Journal of Molecular Sciences, 2021)
(1) Background: Calcium‐binding protein S100B is involved in neuroregeneration but has also been associated with neurodegeneration. These contrasting effects may result from concentration or duration of exposure. We investigated the effect of long‐term increased S100B levels on am-yloid‐β processing in one‐year‐old transgenic (tg) mice with 12 copies of the murine S100B gene with specific consideration of sex and specific brain regions. (2) Methods: S100B and amyloid‐β 42 (Aβ42) were quantified in serum, cerebrospinal fluid (CSF), adipose tissue, and different brain regions by ELISA in wild‐type (wt) and S100Btg mice (each n = 7 per group). Thioflavin T (ThT) and Aβ immunostaining were performed for visualization of Aβ deposition. (3) Results: S100B in serum, CSF, and brain was significantly increased in S100Btg mice of both sexes. Aβ42 was significantly increased in the hippocampus of male S100Btg mice (p = 0.0075), and the frontal cortex of female S100Btg mice (p = 0.0262). ThT and Aβ immunostaining demonstrated Aβ deposition in different brain regions in S100Btg mice of both sexes and female wt. (4) Conclusion: Our data validate this experimental model for studying the role of S100B in neurodegeneration and indicate that Aβ processing is sex‐dependent and brain region‐specific, which deserves further investigation of signaling pathways and behavioral responses.
CRIS-Team Scopus Importer:2021-10-22
Keywords: Alzheimer’s disease; Amyloid‐β processing; Neurodegeneration; S100B; Transgenic mice

Development of pre-syrinx state and syringomyelia following a minor injury: a case report - Kleindienst, Andrea; Engelhorn, Tobias; Röckelein, Verena; Buchfelder, Michael (Journal of Medical Case Reports, 2020)
Background: A generally accepted rule is that posttraumatic syringomyelia (PTS) results from spinal cord injury (SCI). Case presentation: Here, we report the development of syringomyelia without SCI in a 54-year-old Caucasian man following a mild motor vehicle accident. The computed tomography on admission excluded an injury of the spine. Because of neck and back pain, magnetic resonance imaging was performed on day 3 post-injury and demonstrated minimal changes from a ligamentous strain at the cervicothoracic transition. Any traumatic affection of the bone, vertebral discs, intraspinal compartment, or spinal cord were excluded. Some limb weakness and neurogenic bladder dysfunction started manifesting within the following weeks. Repeated MRIs following the accident demonstrated arachnoid adhesions at the C1–2 level and spinal cord edema equivalent to a pre-syrinx state at 12 months and syrinx formation at 24 months. Because of further deterioration, decompression was performed at 36 months. Conclusions: We conclude that even after a minor trauma PTS can occur and that medullary edema (pre-syrinx state) may precede syrinx formation.
CRIS-Team Scopus Importer:2020-11-27
Keywords: Pre-syrinx; Spinal cord injury; Syringomyelia; Trauma; Treatment

Early CSF and Serum S100B Concentrations for Outcome Prediction in Traumatic Brain Injury and Subarachnoid Hemorrhage - Kellermann, Isabel; Kleindienst, Andrea; Hore, Nirjhar; Buchfelder, Michael; Brandner, Sebastian (Clinical Neurology and Neurosurgery, 2016)
OBJECTIVES: S100B has been proposed as a putative biochemical marker in determining the extent of brain injury and corresponding prognosis in neurotrauma. The aim of this study was to evaluate the prognostic value of S100B early concentrations in serum and cerebrospinal fluid (CSF) in traumatic brain injury (TBI) and subarachnoid hemorrhage (SAH), to determine prognostically relevant threshold values and to evaluate fluctuation following EVD placement. PATIENTS AND METHODS: In 102 patients (45 SAH and 57 TBI) under intensive care unit (ICU) treated between January 2011 and December 2012 with external ventricular drain (EVD) S100B measurements were performed simultaneously in serum and CSF during the first 5 days and before and after EVD exchange. Glasgow coma scale (GCS) was assessed on admission and Glasgow outcome scale (GOS) 6 months later. RESULTS: Peak S100B levels in CSF and serum were measured on the first day after admission and concentrations decreased during the ensuing days post injury gradually. CSF and serum S100B concentrations in TBI patients were significantly higher than in SAH (p<0.005). Both in TBI and SAH patients S100B concentrations in CSF and serum were significantly higher in patients with an unfavorable outcome (GOS 1-3) in comparison to patients with a good outcome (GOS 4-5). Correlation of S100B concentrations in serum and GOS score at 6 months was significant both in TBI and SAH (p<0.05). Serum S100B concentrations >0.7μg/l correlated with 100% mortality. Correlation between S100B in CSF and GOS was significant in SAH (p<0.05), whereas it was not significant in TBI. After EVD exchange (n=53) we found a significant increase of S100B concentration in CSF (p<0.005). CONCLUSION: Initial S100B levels have a limited prognostic value in neurotrauma with CSF concentrations being highly sensitive to smallest influences like EVD placement. However, high initial S100B levels of >0.7μg/dl in serum are associated with 100% mortality, which might help to guide therapy strategies in severe neurotrauma.
EVALuna2:33856

How S100B crosses brain barriers and why it is considered a peripheral marker of brain injury - Gayger-Dias, Vitor; Vizuete, Adriana F.K.; Rodrigues, Letícia; Wartchow, Krista Minéia; Bobermin, Larissa; Leite, Marina Concli; Quincozes-Santos, André; Kleindienst, Andrea; Gonçalves, Carlos Alberto (Experimental Biology and Medicine, 2023)
S100B is a 21-kDa protein that is produced and secreted by astrocytes and widely used as a marker of brain injury in clinical and experimental studies. The majority of these studies are based on measurements in blood serum, assuming an associated increase in cerebrospinal fluid and a rupture of the blood–brain barrier (BBB). Moreover, extracerebral sources of S100B are often underestimated. Herein, we will review these interpretations and discuss the routes by which S100B, produced by astrocytes, reaches the circulatory system. We discuss the concept of S100B as an alarmin and its dual activity as an inflammatory and neurotrophic molecule. Furthermore, we emphasize the lack of data supporting the idea that S100B acts as a marker of BBB rupture, and the need to include the glymphatic system in the interpretations of serum changes of S100B. The review is also dedicated to valorizing extracerebral sources of S100B, particularly adipocytes. Furthermore, S100B per se may have direct and indirect modulating roles in brain barriers: on the tight junctions that regulate paracellular transport; on the expression of its receptor, RAGE, which is involved in transcellular protein transport; and on aquaporin-4, a key protein in the glymphatic system that is responsible for the clearance of extracellular proteins from the central nervous system. We hope that the data on S100B, discussed here, will be useful and that it will translate into further health benefits in medical practice.
CRIS-Team Scopus Importer:2023-12-22
Keywords: AQP-4; Astrocyte; BBB; glymphatic system; RAGE; S100B; tight junctions

Hyponatremia in Neurotrauma: The Role of Vasopressin - Kleindienst, Andrea; Hannon, Mark J.; Buchfelder, Michael; Verbalis, Joseph G. (Journal of Neurotrauma, 2016)
Hyponatremia is frequent in patients suffering from traumatic brain injury, subarachnoid hemorrhage, or following intracranial procedures, with approximately 20% having a decreased serum sodium concentration to <125 mmol/L. The pathophysiology of hyponatremia in neurotrauma is not completely understood, but in large part is explained by the syndrome of inappropriate secretion of antidiuretic hormone (SIADH). The abnormal water and/or sodium handling creates an osmotic gradient promoting the shift of water into brain cells, thereby worsening cerebral edema and precipitating neurological deterioration. Unless hyponatremia is corrected promptly and effectively, morbidity and mortality increases through seizures, elevations in intracranial pressure, and/or herniation. The excess mortality in patients with severe hyponatremia (<125 mmol/L) extends beyond the time frame of hospital admission, with a reported mortality of 20% in hospital and 45% within 6 months of follow-up. Current options for the management of hyponatremia include fluid restriction, hypertonic saline, mineralocorticoids, and osmotic diuretics. However, the recent development of vasopressin receptor antagonists provides a more physiological tool for the management of excess water retention and consequent hyponatremia, such as occurs in SIADH. This review summarizes the existing literature on the pathophysiology, clinical features, and management of hyponatremia in the setting of neurotrauma.
EVALuna2:33858

Hypothermia Reduces the Cerebral Blood Flow Threshold Critical to Reestablish Neuronal Membrane Potential - Kleindienst, Andrea; Buchfelder, Michael; Churn, Severn B. (Critical Care Medicine, 2015)
EVALuna2:22863

Longterm Increased S100B Enhances Hippocampal Progenitor Cell Proliferation in a Transgenic Mouse Model - Rodrigues, Leticia; Wartchow, Krista Mineia; Buchfelder, Michael; Souza, Diogo Onofre; Goncalves, Carlos-Alberto; Kleindienst, Andrea (International Journal of Molecular Sciences, 2022)
(1) The neurotrophic protein S100B is a marker of brain injury and has been associated with neuroregeneration. In S100Btg mice rendering 12 copies of the murine S100B gene we evaluated whether S100B may serve as a treatment option. (2) In juvenile, adult, and one-year-old S100Btg mice (female and male; n = 8 per group), progenitor cell proliferation was quantified in the subgranular zone (SGZ) and the granular cell layer (GCL) of the dentate gyrus with the proliferative marker Ki67 and BrdU (50 mg/kg). Concomitant signaling was quantified utilizing glial fibrillary acidic protein (GFAP), apolipoprotein E (ApoE), brain-derived neurotrophic factor (BDNF), and the receptor for advanced glycation end products (RAGE) immunohistochemistry. (3) Progenitor cell proliferation in the SGZ and migration to the GCL was enhanced. Hippocampal GFAP was reduced in one-year-old S100Btg mice. ApoE in the hippocampus and frontal cortex of male and BDNF in the frontal cortex of female S100Btg mice was reduced. RAGE was not affected. (4) Enhanced hippocampal neurogenesis in S100Btg mice was not accompanied by reactive astrogliosis. Sex- and brain region-specific variations of ApoE and BDNF require further elucidations. Our data reinforce the importance of this S100Btg model in evaluating the role of S100B in neuroregenerative medicine.
CRIS-Team WoS Importer:2022-09-16

Nature has no principle-inflammation following brain injury is neither good nor evil* - Kleindienst, Andrea; Buchfelder, Michael; Brandner, Sebastian (Critical Care Medicine, 2014)
EVALuna2:22850

Physiologic MR imaging of the tumor microenvironment revealed switching of metabolic phenotype upon recurrence of glioblastoma in humans - Stadlbauer, Andreas; Oberndorfer, Stefan; Zimmermann, Max; Renner, Bertold; Buchfelder, Michael; Heinz, Gertraud; Dörfler, Arnd; Kleindienst, Andrea; Roessler, Karl (Journal of Cerebral Blood Flow and Metabolism, 2019)
Treating recurrent glioblastoma (GB) is one of the challenges in modern neurooncology. Hypoxia, neovascularization, and energy metabolism are of crucial importance for therapy failure and recurrence. Twenty-one patients with initially untreated GB who developed recurrence were examined with a novel MRI approach for noninvasive visualization of the tumor microenvironment (TME). Imaging biomarker information about oxygen metabolism (mitochondrial oxygen tension) and neovascularization (microvascular density and type) were fused for classification of five different TME compartments: necrosis, hypoxia with/without neovascularization, oxidative phosphorylation, and glycolysis. Volume percentages of these TME compartments were compared between untreated and recurrent GB. At initial diagnosis, all 21 GB showed either the features of a glycolytic dominant phenotype with a high percentage of functional neovasculature (N = 12) or those of a necrotic/hypoxic dominant phenotype with a high percentage of defective tumor neovasculature (N = 9). At recurrence, all 21 GB revealed switching of the initial metabolic phenotype: either from the glycolytic to the necrotic/hypoxic dominant phenotype or vice-versa. A necrotic/hypoxic phenotype at recurrence was associated with a higher rate of multifocality of the recurrent lesions. Our MRI approach may be helpful for a better understanding of treatment-induced metabolic phenotype switching and for future studies developing targeted therapeutic strategies for recurrent GB.
CRIS-Team Scopus Importer:2020-02-21
Keywords: angiogenesis; Glioblastoma; hypoxia; recurrence; treatment failure; tumor microenvironment

Physiologic MR imaging of the tumor microenvironment revealed switching of metabolic phenotype upon recurrence of glioblastoma in humans - Stadlbauer, Andreas; Oberndorfer, Stefan; Zimmermann, Max; Renner, Bertold; Buchfelder, Michael; Heinz, Gertraud; Dörfler, Arnd; Kleindienst, Andrea; Roessler, Karl (Journal of Cerebral Blood Flow and Metabolism, 2020)
Treating recurrent glioblastoma (GB) is one of the challenges in modern neurooncology. Hypoxia, neovascularization, and energy metabolism are of crucial importance for therapy failure and recurrence. Twenty-one patients with initially untreated GB who developed recurrence were examined with a novel MRI approach for noninvasive visualization of the tumor microenvironment (TME). Imaging biomarker information about oxygen metabolism (mitochondrial oxygen tension) and neovascularization (microvascular density and type) were fused for classification of five different TME compartments: necrosis, hypoxia with/without neovascularization, oxidative phosphorylation, and glycolysis. Volume percentages of these TME compartments were compared between untreated and recurrent GB. At initial diagnosis, all 21 GB showed either the features of a glycolytic dominant phenotype with a high percentage of functional neovasculature (N = 12) or those of a necrotic/hypoxic dominant phenotype with a high percentage of defective tumor neovasculature (N = 9). At recurrence, all 21 GB revealed switching of the initial metabolic phenotype: either from the glycolytic to the necrotic/hypoxic dominant phenotype or vice-versa. A necrotic/hypoxic phenotype at recurrence was associated with a higher rate of multifocality of the recurrent lesions. Our MRI approach may be helpful for a better understanding of treatment-induced metabolic phenotype switching and for future studies developing targeted therapeutic strategies for recurrent GB.
EVALuna2:212798

Predicting Glioblastoma Response to Bevacizumab Through MRI Biomarkers of the Tumor Microenvironment - Stadlbauer, Andreas; Roessler, Karl; Zimmermann, Max; Buchfelder, Michael; Kleindienst, Andrea; Dörfler, Arnd; Heinz, Gertraud; Oberndorfer, Stefan (Molecular Imaging and Biology, 2019)
Purpose: Glioblastoma (GB) is one of the most vascularized of all solid tumors and, therefore, represents an attractive target for antiangiogenic therapies. Many lesions, however, quickly develop escape mechanisms associated with changes in the tumor microenvironment (TME) resulting in rapid treatment failure. To prevent patients from adverse effects of ineffective therapy, there is a strong need to better predict and monitor antiangiogenic treatment response. Procedures: We utilized a novel physiological magnetic resonance imaging (MRI) method combining the visualization of oxygen metabolism and neovascularization for classification of five different TME compartments: necrosis, hypoxia with/without neovascularization, oxidative phosphorylation, and aerobic glycolysis. This approach, termed TME mapping, was used to monitor changes in tumor biology and pathophysiology within the TME in response to bevacizumab treatment in 18 patients with recurrent GB. Results: We detected dramatic changes in the TME by rearrangement of its compartments after the onset of bevacizumab treatment. All patients showed a decrease in active tumor volume and neovascularization as well as an increase in hypoxia and necrosis in the first follow-up after 3 months. We found that recurrent GB with a high percentage of neovascularization and active tumor before bevacizumab onset showed a poor or no treatment response. Conclusions: TME mapping might be useful to develop strategies for patient stratification and response prediction before bevacizumab onset.
CRIS-Team Scopus Importer:2019-07-19
Keywords: Angiogenesis; Antiangiogenic therapy; Bevacizumab; Glioblastoma; Hypoxia; Recurrence; Treatment failure; Treatment monitoring; Tumor microenvironment

Psychopathologic Symptoms in Survivors of Critical Illness and Their Relatives-What to Expect From a Screening Tool - Dodoo-Schittko, Frank; Kleindienst, Andrea (Critical Care Medicine, 2019)
CRIS-Team WoS Importer:2019-07-02

QUANTITATIVE MAGNETIC RESONANCE IMAGING CORRELATES WITH EARLY S100B PROFILE AND FUNCTIONAL OUTCOME AFTER ACUTE BRAIN INJURY - Roeckelein, Verena; Kloska, Stephan; Uder, Michael; Buchfelder, Michael; Kleindienst, Andrea (2016)
EVALuna2:14588

Safety and Efficacy of Vaptans in the Treatment of Hyponatremia from Syndrome of Inappropriate Antidiuretic Hormone Secretion (SIADH): A Systematic Review and Meta-Analysis - Krisanapan, Pajaree; Tangpanithandee, Supawit; Thongprayoon, Charat; Pattharanitima, Pattharawin; Kleindienst, Andrea; Miao, Jing; Craici, Iasmina M.; Mao, Michael A.; Cheungpasitporn, Wisit (Journal of Clinical Medicine, 2023)
The utilization of vasopressin receptor antagonists, known as vaptans, in the management of hyponatremia among patients afflicted with the syndrome of inappropriate antidiuretic hormone (SIADH) remains a contentious subject. This meta-analysis aimed to evaluate the safety and efficacy of vaptans for treating chronic hyponatremia in adult SIADH patients. Clinical trials and observational studies were identified by a systematic search using MEDLINE, EMBASE, and Cochrane Database from inception through September 2022. The inclusion criteria were the studies that reported vaptans’ safety or efficacy outcomes compared to placebo or standard therapies. The study protocol was registered with the International Prospective Register of Systematic Reviews (PROSPERO; CRD 42022357307). Five studies were identified, comprising three RCTs and two cohort studies, enrolling a total of 1840 participants. Regarding short-term efficacy on days 4–5, vaptans exhibited a significant increase in serum sodium concentration from the baseline in comparison to the control group, with a weighted mean difference of 4.77 mmol/L (95% CI, 3.57, 5.96; I2 = 34%). In terms of safety outcomes, the pooled incidence rates of overcorrection were 13.1% (95% CI 4.3, 33.6; I2 = 92%) in the vaptans group and 3.3% (95% CI 1.6, 6.6; I2 = 27%) in the control group. Despite the higher correction rate linked to vaptans, with an OR of 5.72 (95% CI 3.38, 9.70; I2 = 0%), no cases of osmotic demyelination syndrome were observed. Our meta-analysis comprehensively summarizes the efficacy and effect size of vaptans in managing SIADH. While vaptans effectively raise the serum sodium concentration compared to placebo/fluid restriction, clinicians should exercise caution regarding the potential for overcorrection.
CRIS-Team Scopus Importer:2023-09-15
Keywords: hyponatremia; satavaptan; SIAD; SIADH; syndrome of inappropriate antidiuresis; syndrome of inappropriate antidiuretic hormone secretion; tolvaptan; V2R antagonists; vaptans; vasopressin receptor antagonist

Screening for Acromegaly in Patients with Carpal Tunnel Syndrome: A Prospective Study (ACROCARP) - Zoicas, Flavius; Kleindienst, Andrea; Mayr, Bernhard; Buchfelder, Michael; Megele, R.; Schöfl, Christof (Hormone and Metabolic Research, 2016)
Early diagnosis of acromegaly prevents irreversible comorbidities and facilitates surgical cure. Carpal tunnel syndrome (CTS) is common in acromegaly and patients have often undergone surgery for CTS prior to the diagnosis of acromegaly. We hypothesized that screening CTS-patients for acromegaly could facilitate active case-finding. We prospectively enrolled 196 patients [135 women, 56.9 (range 23-103) years] who presented with CTS for surgery. Patients were asked about 6 symptoms suggestive of acromegaly using a questionnaire calculating a symptom score (0-6 points), and insulin-like-growth factor 1 (IGF-1) was measured. If IGF-1 was increased, IGF-1 measurement was repeated, and random growth hormone (GH) and/or an oral glucose tolerance test (OGTT) with assessment of GH-suppression were performed. The mean symptom score was 1.7±1.3 points. Three patients reported the maximal symptom score of 6 points, but none of them had an increased IGF-1. There was no correlation between the symptom score and IGF-1-SDS (standard deviation score) (r=0.026; p=0.71). Four patients had an IGF-1>2 SDS. In 2 patients acromegaly was ruled out using random GH and OGTT. One patient had normal IGF-1 and random GH at follow-up. One patient refused further diagnostics. In this prospective cohort of patients with CTS, the observed frequency of acromegaly was at most 0.51% (95% CI 0.03 to 2.83%). In this prospective study, none of the 196 patients with CTS had proven acromegaly. Thus, we see no evidence to justify general screening of patients with CTS for acromegaly.
EVALuna2:2072

Tolvaptan Versus Fluid Restriction in the Treatment of Hyponatremia Resulting from SIADH Following Pituitary Surgery - Kleindienst, Andrea; Georgiev, Simeon; Schlaffer, Sven-Martin; Buchfelder, Michael (Journal of the Endocrine Society, 2020)
Context. The relevance of hyponatremia has been acknowledged by guidelines from the United States (2013) and Europe (2014). However, treatment recommendations differ due to limited evidence.
CRIS-Team WoS Importer:2020-08-21

Treatment of posttraumatic syringomyelia: evidence from a systematic review - Kleindienst, Andrea; Laut, Francisco Marin; Roeckelein, Verena; Buchfelder, Michael; Dodoo-Schittko, Frank (Acta Neurochirurgica, 2020)
Background: Following spinal cord injury (SCI), the routine use of magnetic resonance imaging (MRI) resulted in an incremental diagnosis of posttraumatic syringomyelia (PTS). However, facing four decades of preferred surgical treatment of PTS, no clear consensus on the recommended treatment exists. We review the literature on PTS regarding therapeutic strategies, outcomes, and complications. Methods: We performed a systematic bibliographic search on (“spinal cord injuries” [Mesh] AND “syringomyelia” [Mesh]). English language literature published between 1980 and 2020 was gathered, and case reports and articles examining syrinx due to other causes were excluded. The type of study, interval injury to symptoms, severity and level of injury, therapeutic procedure, duration of follow-up, complications, and outcome were recorded. Results: Forty-three observational studies including 1803 individuals met the eligibility criteria. The time interval from SCI to the diagnosis of PTS varied between 42 and 264 months. Eighty-nine percent of patients were treated surgically (n = 1605) with a complication rate of 26%. Symptoms improved in 43% of patients postoperatively and in 2% treated conservatively. Stable disease was documented in 50% of patients postoperatively and in 88% treated conservatively. The percentage of deterioration was similar (surgery 16%, 0.8% dead; conservative 10%). Detailed analysis of surgical outcome with regard to symptoms revealed that pain, motor, and sensory function could be improved in 43 to 55% of patients while motor function deteriorated in around 25%. The preferred methods of surgery were arachnoid lysis (48%) and syrinx drainage (31%). Conclusion: Even diagnosing PTS early in its evolution with MRI, to date, no satisfactory standard treatment exists, and the present literature review shows similar outcomes, regardless of the treatment modality. Therefore, PTS remains a neurosurgical challenge. Additional research is required using appropriate study designs for improving treatment options.
CRIS-Team Scopus Importer:2020-08-28
Keywords: Etiology; Hydromyelia; Spinal cord injury; Syringomyelia; Trauma; Treatment

Treatment with Cyclic AMP Activators Reduces Glioblastoma Growth and Invasion as Assessed by Two-Photon Microscopy - Wartchow, Krista Mineia; Schmid, Benjamin; Tripal, Philipp; Stadlbauer, Andreas; Buchfelder, Michael; Goncalves, Carlos-Alberto; Kleindienst, Andrea (Cells, 2021)
(1) Background: Despite progress in surgery and radio-chemotherapy of glioblastoma (GB), the prognosis remains very poor. GB cells exhibit a preference for hypoxia to maintain their tumor-forming capacity. Enhancing oxidative phosphorylation-known as the anti-Warburg effect-with cyclic AMP activators has been demonstrated to drive GB cells from proliferation to differentiation thereby reducing tumor growth in a cell culture approach. Here we re-evaluate this treatment in a more clinically relevant model. (2) Methods: The effect of treatment with dibutyryl cyclic AMP (dbcAMP, 1 mM) and the cAMP activator forskolin (50µM) was assessed in a GB cell line (U87GFP+, 104 cells) co-cultured with mouse organotypic brain slices providing architecture and biochemical properties of normal brain tissue. Cell viability was determined by propidium-iodide, and gross metabolic effects were excluded in the extracellular medium. Tumor growth was quantified in terms of area, volume, and invasion at the start of culture, 48 h, 7 days, and 14 days after treatment. (3) Results: The tumor area was significantly reduced following dbcAMP or forskolin treatment (F2,249 = 5.968, p = 0.0029). 3D volumetric quantification utilizing two-photon fluorescence microscopy revealed that the treated tumors maintained a spheric shape while the untreated controls exhibited the GB typical invasive growth pattern. (4) Conclusions: Our data demonstrate that treatment with a cAMP analog/activator reduces GB growth and invasion.
CRIS-Team Scopus Importer:2021-04-16
Keywords: 2-photon-microscopy; glioblastoma; oxidative phosphorylation; treatment; Warburg effect

Treatment with the Neurotrophic Protein S100 Calcium-Binding Protein B Increases Synaptogenesis after Traumatic Brain Injury - Baecker, Justus; Wartchow, Krista; Sehm, Tina; Ghoochani, Ali; Buchfelder, Michael; Kleindienst, Andrea (Journal of Neurotrauma, 2019)
Release of neurotrophic and growth factors such as S100 calcium-binding protein B (S100B) yields an endogenous repair mechanism following traumatic brain injury (TBI). Although nanomolar S100B concentrations enhance hippocampal progenitor cell proliferation, neuronal differentiation, and cognitive recovery, micromolar concentrations may foster inflammatory effects counteracting neuroplasticity. The purpose of the present study was to investigate the effect of S100B on synaptogenesis and microglial activation following experimental TBI. Male Sprague-Dawley rats (n = 40) were subjected to lateral fluid percussion or sham injury, and S100B (50 ng/h) or phosphate buffered saline (PBS) was infused into the lateral ventricle for 7 days using osmotic micropumps. The animals were euthanized on day 5 or, 5 weeks post-injury, and 5 mu m sections, 100 mu m apart (bregma -3.3 to -5.6mm) were analyzed histologically. Cell proliferation was assessed injecting the mitotic marker Bromodeoxyuridine (BrdU) on day 2. S100B enhanced significantly the synaptophysin (SYN) expression and microglial activation (ectodysplasin [ED1]) in the hippocampus in TBI and uninjured sham animals. The glial activation (glial fibrillary acidic protein [GFAP], S100B immunoreactive cells), axonal injury (APP) and cell death (terminal deoxynucleotidyl transferase dUTP nick end labeling [TUNEL]) were not altered. Triple-labelling with BrdU, NeuN, and SYN confirmed a significant participation of S100B in hippocampal synaptogenesis in TBI and uninjured sham animals. Our results demonstrate that S100B augments hippocampal neuro- and synaptogenesis in TBI and uninjured sham animals, thereby improving cognitive function as demonstrated earlier. The S100B-induced microglial activation does not counteract this effect within the first 5weeks. Further studies are required to elucidate respective cellular signaling mechanisms and possible long-term effects.
CRIS-Team WoS Importer:2019-11-26

Ventricular and lumbar cerebrospinal fluid concentrations of Alzheimer's disease biomarkers in patients with normal pressure hydrocephalus and posttraumatic hydrocephalus - Brandner, Sebastian; Thaler, Christian; Lelental, Natalia; Buchfelder, Michael; Kleindienst, Andrea; Maler, Juan Manuel; Kornhuber, Johannes; Lewczuk, Piotr (Journal of Alzheimer's Disease, 2014)
Little information is available on the rostro-caudal concentration gradient of Alzheimer's disease (AD) biomarkers.We studied the concentrations of amyloid-? (A?) peptides 1-42 and 1-40 as well as the Tau and pTau proteins in simultaneously collected ventricular and lumbar cerebrospinal fluid (CSF) samples.The samples were simultaneously collected from the ventricle and the lumbar spinal canal in two groups of patients: 10 subjects being treated for normal pressure hydrocephalus (NPH) by the placement of a ventriculo-peritoneal shunt and 5 patients treated simultaneously with an external ventricular drain and a lumbar CSF drain due to posttraumatic hydrocephalus (PTH).The ventricular-lumbar (V/L) concentration ratio for A?1-40 was 0.81 in NPH patients and 0.71 in PTH patients. The V/L-ratio for A?1-42 was 0.84 in NPH, reflecting significantly higher concentrations in lumbar CSF than in ventricular CSF, and 1.02 in PTH patients. The V/L-ratios for Tau and pTau differed significantly depending on the diagnostic group: the median V/L-ratio for Tau was 6.83 in NPH patients but only 0.97 in PTH patients. The median V/L-ratio for pTau was 2.36 in NPH patients and 0.91 in PTH patients.We conclude that the rostro-caudal concentration gradient for brain-derived proteins (Tau and pTau in this study) depends on the diagnosis and clinical status of the patient, which were largely neglected in the previously postulated models.
EVALuna2:22827